Effects of harmonics in power loss and voltage stability in distribution system / Azwan Ahmad Tajuddin - Tajuddin, Azwan Ahmad (2000)
This project paper is to study the effect of harmonics in power loss and voltage stability in distribution system. A distflow load was developed using C++ programming language to evaluate the power flow voltages and losses in radial distribution network. The results from the load flow analysis are then used to study the effect of the harmonics on distribution loss in each line and voltage stability at load bus. Harmonics are sinusoidal voltages or currents having frequencies that are multiples of the frequency at which the supply system is designed to be operate.